2015
DOI: 10.1590/0102-311x00125014
|View full text |Cite
|
Sign up to set email alerts
|

Atividades avançadas de vida diária e incidência de declínio cognitivo em idosos: Estudo SABE

Abstract: O objetivo deste trabalho foi avaliar o impacto das atividades avançadas de vida diária (AAVD) na incidência de declínio cognitivo. A amostra foi composta por idosos participantes do estudo longitudinal Saúde, Bem-estar e Envelhecimento (SABE). O declínio cognitivo foi avaliado por meio do Mini - Exame do Estado Mental abreviado. As AAVD compreenderam 12 atividades sociais, produtivas, físicas e de lazer que envolvem funções cognitivas superiores. Foram considerados grupos de covariáveis do estudo: fatores soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
2
33

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 48 publications
3
33
2
33
Order By: Relevance
“…According to the authors, these results can be explained by the diversity of stimuli involved in each type of AADL studied and the differences of intensity, frequency and duration in the performance of those activities. 38 This study has some limitations. First, the engagement in AADLs was measured through the self-reporting of the elderly individuals.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…According to the authors, these results can be explained by the diversity of stimuli involved in each type of AADL studied and the differences of intensity, frequency and duration in the performance of those activities. 38 This study has some limitations. First, the engagement in AADLs was measured through the self-reporting of the elderly individuals.…”
Section: Discussionmentioning
confidence: 91%
“…When sociodemographic variables were considered using the multivariate analysis model, an inverse relationship was observed between engagement in physical activity and cognitive performance, and there was also no association between performance of social activities and cognitive performance. The SABE 38 project assessed the impact of AADLs (physical, social, productive and leisure) on the incidence of cognitive decline among non-institutionalized elderly over a mean period of four years. The results showed that elderly individuals who did not develop cognitive decline, on average performed significantly more AADLs than those who did.…”
Section: Discussionmentioning
confidence: 99%
“…A literatura destaca a importância do trabalho no cotidiano, tendo papel central na vida adulta, gerando remuneração e favorecendo a integração social, mediante o compartilhamento de experiências com os outros e da realização de atividades que lhe fazem sentido e lhe fornecem um status social 1,22,23,24,25,26 .…”
Section: Discussionunclassified
“…Estas últimas exigem como expectável, maiores níveis de funcionalidade (Dias, Andrade, Duarte, Santos e Lebrão, 2015). O declínio cognitivo pode associar-se a um padrão específico de perdas funcionais das AVD.…”
Section: Introductionunclassified
“…O declínio cognitivo pode associar-se a um padrão específico de perdas funcionais das AVD. Estas perdas de funcionalidade iniciam-se com um comprometimento nas AAVD, seguidas pelas AIVD e por último pelas ABVD (Dias et al, 2015). Os autores (Ibidem) reforçam a ideia de que a preservação do desempenho das AVD é um fator protetor na conservação das funções mentais.…”
Section: Introductionunclassified